The underground argon project: procurement and purification of argon for dark matter searches and beyond - Agnes, P.; Back, H. O.; Bonivento, W.; Boulay, M. G.; Canci, N.; Caravati, M.; Cebrian, S.; Cocco, V.; Diaz Mairena, D.; Franco, D.; Gabriele, F.; Gahan, D.; et al. (Frontiers in Physics, 2024)
The existence of dark matter in the Universe is inferred from abundant astrophysical and cosmological observations. The Global Argon Dark Matter Collaboration (GADMC) searches for dark matter in the form of weakly interacting massive particles (WIMPs), whose collisions with argon nuclei would produce nuclear recoils with tens of keV energy.Argon has been considered an excellent medium in the direct detection of WIMPs as argonbased scintillation detectors can make use of pulse shape discrimination (PSD) to separate WIMP-induced nuclear recoil signals from electron recoil backgrounds with extremely high efficiency.However, argon-based direct dark matter searches must confront the presence of intrinsic 39 Ar as the predominant source of electron recoil background (it is a beta emitter with an endpoint energy of 565 keV and half-life of 269 years). Even with PSD, the 39 Ar activity in atmospheric argon, mainly produced and maintained by cosmic ray induced nuclear reactions, limits the ultimate size of argon-based detectors and restricts their ability to probe very low energy events.The discovery of argon from deep underground well with significantly less 39 Ar than atmospheric argon was an important step in the development of direct dark matter detection experiments using argon as the active target.